(untitled) (Web of Teachers: Inderscience Research, 2025)
The clinical and laboratory characteristics and its metabolic determinants, in which hypocalcemic convulsive syndrome occurs in young children, are one of the pressing issues in the framework of modern pediatric and neurological sciences. Hypocalcemia is a condition caused by a decrease in calcium levels in the blood, which can manifest mainly in acute and chronic forms in young children. This, in turn, affects the functioning of the central nervous system, leading to the appearance of clinical signs in the form of convulsions, that is, uncontrolled muscle contractions. Hypocalcemic convulsive syndrome is often associated with metabolic disorders, and its etiology, pathogenesis, clinical manifestations and coverage of diagnostic signs are of great importance in improving the health of young children.